2021
DOI: 10.1155/2021/3847347
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Confirmation of Vancomycin-Resistant Staphylococcus aureus with vanA Gene from a Hospital in Kathmandu

Abstract: Staphylococcus aureus, a commensal on the skin and in the nasal cavity of humans, is one of the most serious cases of nosocomial infections. Moreover, methicillin-resistant S. aureus (MRSA) is a leading cause of morbidity and mortality worldwide. For the treatment of MRSA infections, vancomycin is considered as a drug of choice. However, the emergence of vancomycin resistance among MRSA isolates has been perceived as a formidable threat in therapeutic management. To estimate the rate of vancomycin-resistant S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 42 publications
(44 reference statements)
1
17
2
Order By: Relevance
“…SFP is characterized by gastroenteritis and has been recognized as one of the main culprits of food poisoning epidemics worldwide [ 39 ]. Methicillin-resistant strains of S. aureus (MRSA) have recently been classified as high priority bacteria with the potential to cause devastating mortality globally if adequate treatment options are not developed [ 40 ]. The presence of coagulase-positive Staphylococci in the Gbeli remains very worrying.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SFP is characterized by gastroenteritis and has been recognized as one of the main culprits of food poisoning epidemics worldwide [ 39 ]. Methicillin-resistant strains of S. aureus (MRSA) have recently been classified as high priority bacteria with the potential to cause devastating mortality globally if adequate treatment options are not developed [ 40 ]. The presence of coagulase-positive Staphylococci in the Gbeli remains very worrying.…”
Section: Resultsmentioning
confidence: 99%
“…The fourth section was related to type of seller, while the last section was related to hygiene and production conditions (source of water, kind of packaging materials, personal hygiene of vendors, environmental sanitation, etc.). It should be noted that forty (40) producers were assisted during Gbeli production in your industrial units in order to identify all steps and conditions of the production. After each interview step, Gbeli ready-to-eat (100 g) were aseptically sampled from vendors at the point of sale.…”
mentioning
confidence: 99%
“…18 In this study, majority of the MRSA were isolated from pus sample which is in accordance with findings of other studies in various places and time duration. [7][8][9]15,16 Staphylococci are predominant etiology of suppurative infections that signifies reason for its high prevalence among pus specimen. 18 According to various literatures, MRSA prevalence is more common among inpatients.…”
Section: Discussionmentioning
confidence: 99%
“…2 MRSA was reported first time in Nepal in 1990 by Rai et al 3 After that, MRSA have been reported frequently along with recent VRSA infection in our country. [4][5][6][7][8] Resistance genes like mecA and vanA responsible for methicillin and vancomycin resistance respectively, have been reported from various countries including Nepal. [8][9][10][11] Severe infections with MRSA, mediated by PVL gene, also have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation